Upgrade of the CMS resistive plate chambers for the high luminosity LHC. (1st January 2022) - Samalan, A.; Tytgat, M.; Alves, G.A.; Marujo, F.; Torres Da Silva De Araujo, F.; Da Costa, E.M.; De Jesus Damiao, D.; Nogima, H.; Santoro, A.; Fonseca De Souza, S.; Aleksandrov, A.; Hadjiiska, R.; et al.
Abstract: During the upcoming High Luminosity phase of the Large Hadron Collider (HL-LHC), the integrated luminosity of the accelerator will increase to 3000 fb −1 . The expected experimental conditions in that period in terms of background rates, event pileup, and the probable aging of the current detectors present a challenge for all the existing experiments at the LHC, including the Compact Muon Solenoid (CMS) experiment. To ensure a highly performing muon system for this period, several upgrades of the Resistive Plate Chamber (RPC) system of the CMS are currently being implemented. These include the replacement of the readout system for the present system, and the installation of two new RPC stations with improved chamber and front-end electronics designs. The current overall status of this CMS RPC upgrade project is presented.